(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
Academic freedom is a term whose practical implementation represents a challenge and, therefore, its reflection must be critical and iterative. Under this premise, this document aims to build a discussion around the conceptualization and meanings of academic freedom through a documentary review of the concept and the collection of both institutional and faculty discourses. In this study, a short interview is conducted with faculty members of the Escuela de Geografía and the legal advisor to the Vicerrectoría de Docencia at the University of Costa Rica, understanding that this institution is the framework in which academic freedom is exercised as a fundamental principle. The analysis of the findings allows us to present a self-assessment tool aimed at practicing professors who wish to evaluate their degree of awareness of academic freedom through their knowledge and pedagogical decisions. With this tool, they will be able to identify those notions that allow them to develop a critical, reflective, and conscious stance on the relationship between teaching practice, academic freedom, and its limits.